Mapping Ecosystem Services - Joachim Maes (Pensoft Publishers, 2017)
The EU Biodiversity Strategy to 2020 called on Member States to map and assess the state of ecosystems and their services in their national territory by 2014, with the assistance of the European Commission. Mapping ecosystem services constitutes a very powerful tool to bring ES into practical application. Being able to efficiently communicate complex spatial information, ES maps are very useful for raising awareness about areas of ecosystem services supply and demand. Furthermore, maps are mandatory instruments for landscape planning, environmental resource management and land use optimization. This book is an excellent summary of the achievements of ecosystem service mapping and provides guidance for scientists, students, practitioners and decision makers who need to map ecosystem services.